Academic tutoring and the collaboration between tutor and professor as a guiding force for student professional identity - Kavalek, Débora Schmitt; Pessoa, Jadson Laranjeira (Brazilian Journal of Production Engineering, 2023)
The transition to Higher Education often challenges students, particularly in understanding complex concepts, such as chemistry. To address this issue, academic mentoring projects emerge as a valuable alternative. This experience report discusses the role of the academic monitor in promoting learning, with a focus on building a strong foundation in chemistry knowledge. The monitor, a student in the Bachelor of Science program, actively participated in mentoring projects in two curriculum components at the Federal University of Southern Bahia (UFSB). Their work involved close collaboration with the professor to assist students with difficulties in understanding chemical concepts. This included careful observation of students, analysis of their profiles, and the development of personalized teaching strategies. The monitor used visual resources, such as videos, to enhance students’ comprehension. Additionally, online tutoring sessions were held to address doubts. This experience report highlights the importance of academic mentoring in shaping the professional identity of students, promoting effective learning, and contributing to the advancement of scientific knowledge. This study presents a practical approach that can be beneficial for educators and students seeking to improve the teaching and learning process in Higher Education, emphasizing the positive impact of academic mentoring on the development of graduates.